INFLUENCE OF THE VISUAL NOVEL GAME PROJECT SEKAI: COLORFUL STAGE! AS AUDIO VISUAL MEDIA FOR MOTIVATION TO LEARN JAPANESE VOCABULARY - Nurhaliza, Raisa Siti; Setiana, Soni Mulyawan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
In Indonesia, Japanese is one of the most rapidly increasing languages. The growing number of people studying Japanese for the sake of academics, communication, and professional purposes proves. From the variety of characters, the grammar, and the language used, it is possible to identify the form of the language. The motivation to learn a second language can be an important factor. The motivation of learners in learning is, of course, dependent on their interests. The purpose of this research is to analyze a visual novel game called Project Sekai: Colorful Stage! as a trigger to increase motivation to learn, especially Japanese vocabulary, and how this trigger occurs. By collecting data using a closed questionnaire for the project Sekai: Colorful Stage! players, this research will use a quantitative description method.